The Relevance of Law: Some Determinants of Identifying - ONISHCHENKO, Nataliya M.; BOBROVNYK, Svitlana V. (Journal of Advanced Research in Law and Economics, 2019)
The relevance of the research is due to the fact that the topic of the importance of law as a regulator of social relations is one of the most interesting and little-studied topics of general application of law. In this context, the article is dedicated to the determinants of the relevance of law as a regulator of social relations. Among such determinants there is temporal component, awareness of law, emotional perception of law and so on. As well as the consideration of certain factors that affect the effectiveness of regulatory and security functions of law. The materials of the research have practical significance for university professors of law specialties.